2020
DOI: 10.1002/hep4.1492
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for Implementing Hepatitis C Virus Care in Homeless Shelters: The Stakeholder Perspective

Abstract: Compared with the general population, homeless individuals are at higher risk of hepatitis C infection (HCV) and may face unique barriers in receipt of HCV care. This study sought the perspectives of key stakeholders toward establishing a universal HCV screening, testing, and treatment protocol for individuals accessing homeless shelters. Four focus groups were conducted with homeless shelter staff, practice providers, and social service outreach workers (n = 27) in San Francisco, California, and Minneapolis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
54
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 32 publications
5
54
0
Order By: Relevance
“…In an earlier pilot study in homeless centers (67%; [ 12 ]) and in studies from the USA, linkage ranged from 66% for inpatient and 58% for outpatient populations to 23% for people visiting the emergency department. This finding suggests that the guidance provided by the hepatitis ambassadors and hospital staff was successful, thereby supporting earlier recommendations [ 13 , 27 ]. A qualitative study among homeless people in the USA has suggested that a designated HCV coordinator, an incentive for clients to continue follow-up appointments, reduced treatment periods (to a maximum 2 months), education of personnel and HCV-positive patients, and peer support for HCV patients are needed to promote linkage to care [ 27 ].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In an earlier pilot study in homeless centers (67%; [ 12 ]) and in studies from the USA, linkage ranged from 66% for inpatient and 58% for outpatient populations to 23% for people visiting the emergency department. This finding suggests that the guidance provided by the hepatitis ambassadors and hospital staff was successful, thereby supporting earlier recommendations [ 13 , 27 ]. A qualitative study among homeless people in the USA has suggested that a designated HCV coordinator, an incentive for clients to continue follow-up appointments, reduced treatment periods (to a maximum 2 months), education of personnel and HCV-positive patients, and peer support for HCV patients are needed to promote linkage to care [ 27 ].…”
Section: Discussionsupporting
confidence: 82%
“…A qualitative study among homeless people in the USA has suggested that a designated HCV coordinator, an incentive for clients to continue follow-up appointments, reduced treatment periods (to a maximum 2 months), education of personnel and HCV-positive patients, and peer support for HCV patients are needed to promote linkage to care [ 27 ]. Unstable accommodation in particular is a major barrier for HCV treatment uptake [ 28 , 29 , 30 ], which could be overcome by extending shelter stays for HCV-positive clients [ 27 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Homelessness in itself is also a risk factor for HIV infection [ 26 ]. This could be explained because independent risk factors, such as injection drug use, engaging in unsafe injection drug‐use practices, mental health disorders, and a history of incarceration, are common in this population [ 27 , 28 ]. Our study is in accordance with previous estimates of HIV prevalence among PWUD in Western and Central Europe [ 29 ], and confirms the higher HIV prevalence in homeless PWUD screened and people with a longer drug injection duration.…”
Section: Discussionmentioning
confidence: 99%
“…It reduces the quality of sound health and significantly contributes to mortality and morbidity as well. The virus is responsible for transfusion-associated non-A non-B Hepatitis was identified and later named with Hepatitis C (HCV) in 1989 (Fokuo et al 2020).…”
Section: Introductionmentioning
confidence: 99%